The Impact of Home Production on Economic Inequality in Germany - Joachim R. Frick; Markus M. Grabka; Olaf Groh-Samberg (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Using representative income and time use-data from the German Socio-Economic Panel (SOEP), we estimate non-monetary income advantages arising from home production and analyse their impact on economic inequality. As an alternative to existing measures, we propose a predicted wage approach based on a bias-adjusted measure of hours spent on home production. Sensitivity analyses comparing results obtained from different approaches provide indications of methodological effects arising from the choice of method. Although the substantive notion of reduced inequality is stable, the degree of variation in our findings underscores the need for a harmonized approach in cross-nationally comparative research.
Keywords: D31; D13; I32; 330; Home Production; Non-Cash Incomes; Economic Inequality; Well-being; SOEP